1997
DOI: 10.1103/physrevb.56.7285
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical analysis of the magnetic circular dichroism in the2p3dand2p4dx-ray emission of Gd

Abstract: The 2p3d and 2p4d x-ray emission spectral shapes have been calculated using a theoretical description of spin-polarized 2p photoemission and atomic multiplet calculations of the 2 p3d and 2p4d radiative decay. Emphasis is given to the use of circular-polarized x rays for the excitation process. Good agreement with experiment is found and all visible experimental structures can be explained. It is shown that because of weak multiplet effects in the intermediate state, it is possible to use the incoherent, two-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…The angles and are taken as 60 and 30°, respectively. The calculated results (de Groot et al, 1997) with a Gd 3ϩ ion model are also shown with the solid curves. The agreement with the experimental results is good.…”
Section: E Polarization Dependence and Magnetic Circular Dichroismmentioning
confidence: 99%
See 2 more Smart Citations
“…The angles and are taken as 60 and 30°, respectively. The calculated results (de Groot et al, 1997) with a Gd 3ϩ ion model are also shown with the solid curves. The agreement with the experimental results is good.…”
Section: E Polarization Dependence and Magnetic Circular Dichroismmentioning
confidence: 99%
“…VI.B. de Groot et al (1997) considered the situation in which a photon with circular polarization (ϩ or Ϫ helicity) is incident on the sample with the angle from the sample surface normal, and the emitted photon is detected with the angle from the surface normal without analyzing the polarization, where the surface normal is perpendicular to the magnetization of the sample, and all the directions of incident and emitted photons, surface normal and the magnetization are in the same plane. Then they showed that the MCD of RIXS, i.e., the difference of RIXS for the incident photons with ϩ and Ϫ helicities, is given by…”
Section: E Polarization Dependence and Magnetic Circular Dichroismmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic dichroism measurements have been combined with RIXS previously, but these studies were mainly performed at the L 2;3 absorption edges, probing low energy transfer excitations in 3d TM [20,21] or the quadrupole transitions (2p ! 4f) in lanthanides [22][23][24][25][26].The 1s2p RIXS probes the evolution of K emission (2p ! 1s) following resonant excitation of a 1s electron.…”
mentioning
confidence: 99%
“…MCD in RIXS experiments performed at the Gd L3-edge [47] Experiments exploiting magnetic linear dichroism (MLD) have also been implemented for Yb [45]. As pointed out in [45], such MLD x-ray fluorescence experiments do not clear up ambiguities in the interpretation of x-ray absorption because the RIXS process is dominated by 4d − 4f interactions in the final state. It is doubtful, therefore, that magnetic dichroism have a direct impact on our understanding of how XMCD scales to the 4f or 5d moments [48,49].…”
Section: Magnetismmentioning
confidence: 98%